KERATON DAN OTORITAS: RELOKASI PEMUKIMAN WARGA DALAM BENTENG KERATON YOGYAKARTA - Hawawi, Alfina; Qomar, Subaidi (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to analyze the research related to the Palace and its Authority in the Beteng Keraton revitalization program with the policy of relocating community settlements in the area. This study is qualitative with the theory and concept of social structure and legal rationality and Max Weber's bureaucracy. The data in this study were collected through observation, interview, and documentation techniques involving the community who live within the scope of the Benteng Keraton and are currently being relocated. The results of this study indicate that the community has awareness and openness to the procurement of relocation by the Palace. The community accepts the consequences even though there are various difficulties experienced. The palace is not arbitrary towards the community because it continues to carry out good and orderly procedures such as implementing socialization and providing interest or severance pay. With the actions and good relations between the palace and the community, harmonious conditions are created without conflict. In addition, the existence of legitimate laws and regulations of the Palace makes the community accept whatever has become the decision of the Palace Government. This is the authority that the Palace has in a democratic system that is based on the principles of humanity and equality.